The economics of repressed inflation - Charlesworth, Harold Kerr. (London ; New York : Routledge, 2003)
This microeconomic analysis suggests that the combination of inflationary pressures and the control of consumption has economic effects on the price level and on the distribution of resources which may be as serious for the economy as the more widely recognized effects of an uncontrolled inflation.
Includes index.
Includes bibliographical references.
rpm 21/09/16
Loans
Keywords: Inflation (Finance); Inflation (Finance) -- Great Britain; Currency question; Currency question -- Great Britain; Great Britain